MODELS TO ESTIMATE CHILLING ACCUMULATION UNDER SUBTROPICAL CLIMATIC CONDITIONS IN BRAZIL - Milech, Chaiane Gouvea; Scariotto, Silvia; Dini, Maximiliano; Herter, Flávio Gilberto; Raseira, Maria do Carmo Bassols (Revista Brasileira de Climatologia, 2021)
Chilling requirement is a characteristic that limits temperate fruit crops cultivation under subtropical climate. Several mathematic models, differing on the relative value of chilling units have been developed, in order to estimate the chilling accumulation on a given site. The present work compared eight of these models using data from hourly temperatures from May to August, from a period of 11 years, collected in Pelotas, RS, Brazil, aiming to characterize the region regarding the chilling accumulation for the cultivation of deciduous fruit trees and it also had as objective to check if a model using average temperatures is suitable enough to be used when hourly temperatures were not available. The eight tested models were: Chilling Hours (≤7.2°C); Chilling Hours (≤11°C); Utah; Low Chill; Dynamic; Mean Temperatures; Positive Utah and Taiwan. The results showed large differences between years, regardless of the used model. However, the Taiwan and Low Chill models seemed more suitable for the estimation of the accumulation of cold in the Pelotas region. The Medium Temperatures model can be used as a valid option since it has a high correlation with the other models and easy data availability.